Willingness to Communicate: The Predictive Roles of the L2 Motivational Self-System and Self-Efficacy - Farnaz Esmkhani Youvalari (Yayasan Visi Intan Permata, 2021)
Research on communication emphasizes the psychological variables that play a great role in predicting a predisposition for engaging or avoiding communicative behavior. As a quantitative correlational study, this research was conducted with a convenient sample of 94 Iranian EFL learners to investigate to what degree the L2 motivational self-system and self-efficacy beliefs of language learners could predict second language willingness to communicate (WTC). A Likert scale highly reliable questionnaire containing 35 items was put to use to collect data on dimensions of the L2 motivational self-system, self-efficacy beliefs and L2 WTC. After the combined predictive ability of these variables, as a model, on WTC was measured, the study aimed at finding the unique contribution of each variable on WTC. Also, the researcher aimed at investigating whether gender would moderate each of the relationships between the explanatory variables and WTC. A set of multiple regression analyses indicated that the ideal L2 self, the ought-to L2 self, the L2 learning experience, and self-efficacy, as a whole model, was able to predict 41.6% of the variation in WTC. It was found that the ideal L2 self was the strongest predictor of WTC, followed by self-efficacy beliefs, which uniquely explained 38.7% and 16.8% of the variation in WTC scores, respectively. Additionally, it was observed that gender did not have the ability to statistically moderate any of the aforementioned relationships. The findings of this academic endeavor are discussed in relation to the potential theoretical and practical implications it has for the field of English language teaching.